Substituição de uréia por cloreto de amônia em dietas de bovinos : digestibilidade, síntese de proteina microbiana, parâmetros ruminais e sanguíneos - Castañeda Serrano, Román David (2008)
This study was conducted to evaluate effects of replacing urea with ammonium chloride in cattle diets on total apparent digestibility of nutrients, rumen and plasma parameters, and synthesis of microbial protein. Five Holstein steers weighting 450 kg were used. Statistical design was a Latin square 5 x 5, where treatments consisted of five replacement levels, 0, 25, 50, 75 and 100% of urea by ammonium chloride. There was a linear decrease (P<0.05) on intake of DM, OM, CP, NDF and EE as result of ammonium chloride inclusion in diet. There was a linear increase (P<0.05) on fecal flow and on total apparent digestibility (P<0.05) of DM, OM, CP and NDF, and on TDN as urea was replaced by ammonium chloride. There was a quadratic effect (P<0.05) as result of ammonium chloride use. Urine volume increased linearly (P<0.05) when urea was replaced by ammonium chloride. However, treatments did not influence (P>0.05) daily excretion of allantoin, purine derivatives, absorbed purines, as well as microbial nitrogen compounds and microbial efficiency synthesis. Replacement of urea by ammonium chloride produced a linear increase (P< 0.05) on uric acid excretion in urine. Rumen pH decreased linearly (P<0.05) but treatments did not influence (P>0.05) ammonia concentration in the rumen as urea was replaced by ammonium chloride. on urea nitrogen in plasma with the ammonia chloride inclusion produced a linear decrease. These results show a possible use of ammonia chloride as NPN source for cattle, but it is important to considerer that increased levels of ammonium chloride decrease intake. Results suggest that ammonium chloride could give a more efficient utilization of N in the rumen, and such fact could be better understood in diets with high concentration of non-fibrous carbohydrates.